PERAN AEOI DALAM KETERBUKAAN INFORMASI PAJAK UNTUK MENINGKATKAN PENERIMAAN PAJAK DI INDONESIA - Yona Millenia Febyani; Jumiyanto Widodo (Universitas Diponegoro, 2020)
In the era of globalization and technological advances, global economic integration has an impact on Indonesia's taxation sector. Writing this journal discusses the role of AEoI in disclosing tax information to increase tax revenue in Indonesia. The research objective is to study and analyze the role of the AEoI in increasing state revenue from the tax sector in Indonesia. Research using literature studies, based on the data obtained and studied, it can be seen through the AEoI that information disclosure occurs which can increase tax revenue. The convenience provided by technology has a positive impact on taxpayers, but it cannot be denied that there are negative taxpayer practices such as tax avoidance and tax evasion which can lead to a decrease in potential tax revenue. Tax avoidance and evasion practices involve tax haven countries which make it difficult to eradicate domestic institutions. Cooperation between countries in the field of taxation is needed to overcome tax avoidance and evasion practices through the OECD program related to transparency and automatic disclosure of information, namely the Automatic Exchange of Information (AEoI). One form of Indonesia's commitment in implementing AEoI is to issue PERPPU No. 1 of 2017 concerning Access to Financial Information for Taxation Purposes. The application of AEoI in Indonesia can strengthen the tax base so that state revenue from the tax sector becomes more optimal.